Important role of the government in reducing pesticide use and risk sustainably in Thailand: Current situation and recommendations - Sapbamrer, Ratana; Kitro, Amornphat; Panumasvivat, Jinjuta; Assavanopakun, Pheerasak (Frontiers in Public Health, 2023)
Agriculture is an important aspect of Thailand's GDP and development. It ranks as the 8th largest exporter in the world, however, pesticide use associated with the agriculture is ranked 18th in the world and 5th in Asia. Previous studies have clearly stated that pesticides are a threat to human health and the environment. The government is now making efforts to address pesticide use and the health impacts of pesticide use, however, these efforts are still in need of completion. This paper aims to summarize: (1) the current situation with regard to pesticide use in Thailand; (2) the current situation with regard to pesticide poisoning in Thailand; and (3) important role of government in reducing pesticide use and risk sustainably in Thailand: current situation and recommendations. This article suggests that government is a significant driver for reducing pesticide use and risk sustainably and the establishment of push and pull policies, legislation, and strategies. The government needs to strictly adhere to international conventions. Introducing a pesticide tax is essential to reduce redundant pesticide use. Updating of the current act, specific regulations with regard to pesticides and strict enforcement are urgently required. Licensing pesticide applicators should be implemented continuously. Promotion of alternative pest management is needed by supportive production inputs, technology, and markets as well as the development of a monitoring and certification system. Educating consumers on how to choose safe agricultural products and reduce risk from pesticide residues in the products is also necessary. All approaches should be implemented simultaneously and instantly. Importantly, the government needs to cooperate with agricultural sectors, health and environmental sectors, private sectors, as well as food industries to tackle complicate issues in a sustainable manner and lower pesticide use and risk sustainably in Thailand.